Industrial growth and world trade : an empirical study of trends in production, consumption and trade in manufactures from 1899-1959, with a discussion of probable future trends - Maizels, Alfred (Cambridge [Eng.] : University Press, 1963)
This is comprehensive world-wide study of both production and trade patterns of manufactures through time series (1899-1959) and cross- section studies. The book provides much information on trading relationships among the advanced industrial nations and also compare the experience of the poor semi-industrial countries to the rich industrial ones. This comparison provides much useful information for both inter- national trade and economic development theorists.
Includes index
Includes bibliographical references: p. 549-556.
II 17/01/2019
Loans
Keywords: Commerce; Industrialization; Trade